Upon this rock [videorecording] - Dault, Gary Michael; Garwood, Joseph J.; McGreevy, John; Puncher, Jennifer; Ustinou, Peter Sir (Inside the Vatican, 1993)
A tour in the Vatican's inner sanctums, secret archives, Vatican grottos, coloseum in the days of the Roman empire and Constantinople now Istanbul, a mysterious Eastern outpost of Christianity. A reenacted interviews with Emperor Constantine and Pope Gregory the Great.